PENGARUH JENIS KEMASAN RETORT POUCH TERHADAP KARAKTERISTIK DAGING IGA DALAM SOP IGA READY TO EAT - Ikrawan, Yusep; Laverta, Tiar; Yelliantty, Yelliantty (Department of Food Technology, Universitas Pasundan, Bandung, 2025)
The purpose of this study was to determine the differences in the characteristics of rib eye meat in instant rib soup using nylon retort and aluminum retort packaging in a vacuum. The method used in this study is the paired samples T test with the application of Statistical Package for the Social Sciences (SPSS) version 22.0. This design consists of two variables, namely the response to the nylon retort pouch packaging and the response to the aluminum retort pouch packaging. The parameters tested consisted of four responses, namely, water content using the gravimetric method, pH value using the pH meter method, total microbes using the Total Plate Count (TPC), and organoleptic using the hedonistic quality test. The results of this study showed that the water content, pH value, and total microbes in rib eye meat in instant rib soup using nylon retort pouch packaging had no or an insignificant difference with the water content, pH value, and total microbes in rib eye meat in instant ribs using aluminum packaging. retort pouch for twenty-one days of storage. The results of the organoleptic response on the scent and texture attributes of ribs in aluminum retort pouch packaging are different from ribs that are packaged in nylon retort pouches and without sterilization. In terms of color and taste attributes of unsterilized ribs packaged with nylon retort pouches and aluminum retort pouches, there was no significant difference.